Comparison of revegetation techniques on mineral clay soil: analysis of quantitative response of vegetation cover - Muzzi, Enrico; Mongardi, Gabriele (Italian Journal of Agronomy, 2016)
Revegetation of mineral-clay soils is a notably complex ecological and technically challenging undertaking that depends on substrate profile and local micro-environmental conditions, factors making it a particularly long procedure as well. This study compared and assessed the medium-term effectiveness of four treatments employed to promote stable pedogenesis and herbaceous recolonisation of abandoned clay quarries in the Apennine foothills of northern Italy’s Emilia- Romagna region. The treatments included: slow-release N organic fertiliser, phosphate fertiliser, organic amendment and topsoil [the soil top layer (0-0.2 m) of a local natural meadow]. The state of the vegetative cover was monitored monthly from 1994 through 2004, until problems of slope stability at the site compromised the integrity of the trial plots. Significant effects were achieved by the recycled topsoil through 8 years and by organic amendment through 6 years; the effects of slow-release nitrogen were notably limited over time and phosphorous delivered a medium-term response but of notable year-toyear swings. No interactions among factors emerged in the mediumterm. After 11 years, treatments did not induce effects statistical appreciable. Our results suggest that the tested agronomic strategies on mineral clay soil did not trigger, in the medium-term, secondary succession processes able to potentially alter the spontaneous revegetation course.